2015
DOI: 10.1002/macp.201500296
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Protein Nanogels Prepared by In Situ Polymerization

Abstract: Proteins with unique structure and function have tremendous applications for cancer treatment, vaccination, diagnosis, regenerative medicine, and therapies for loss‐of‐function genetic diseases. A general method of loading and delivering active forms of proteins toward cells and tissues is highly desirable for remaining activity, enhancing stability, and avoiding potential immunogenicity of proteins. Nanogels with cross‐linked structure provide a versatile platform for storage and release of proteins. Herein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 68 publications
(128 reference statements)
0
21
0
Order By: Relevance
“…Recent studies have demonstrated the disruption of nanogels by using cross-linking agents sensible to temperature, light, differences in pH, use of disulfide bond linkages and cleavage by glutathione (GSH) enzyme. Therefore, the active principle can reach intracellular targets after nanogels are endocytosed, promoting endolysosome escape and improving intracellular therapy [ 59 , 60 , 61 ].…”
Section: Polymeric Nanocarriers Against Intracellular Infections: mentioning
confidence: 99%
“…Recent studies have demonstrated the disruption of nanogels by using cross-linking agents sensible to temperature, light, differences in pH, use of disulfide bond linkages and cleavage by glutathione (GSH) enzyme. Therefore, the active principle can reach intracellular targets after nanogels are endocytosed, promoting endolysosome escape and improving intracellular therapy [ 59 , 60 , 61 ].…”
Section: Polymeric Nanocarriers Against Intracellular Infections: mentioning
confidence: 99%
“…Protein drugs can be used to directly replace the dysfunctional endogenous protein and are applicable to a variety of cancer treatments, vaccinations and therapies for genetic disorders [4648]. Additionally, because of the specific functionality and structural hierarchy, therapeutic proteins mitigate the side-effects of interference with the biological system [49,50]. However, the intrinsic properties of the therapeutic protein also pose significant challenges for the full potential of its transdermal delivery [49,51,52].…”
Section: Types Of Delivered Proteinmentioning
confidence: 99%
“…Moreover, after functionalization or conjugation of other molecules, the protein properties and functions might be altered. In recent years, encapsulation of proteins by in situ polymerization was developed as an alternative strategies for protein modification (Ye et al, 2016b ). The protein nanogels were obtained by incorporation of cross-linkers to protein surface and polymerization.…”
Section: Othersmentioning
confidence: 99%